Promoting civility in nursing education and practice: A systematic literature review - Juneivent Saputra Datu Hanggamara; Leny Felinia; Putry Sisilia Witak; Ni Gusti Ayu Eka; Windy Sapta Handayani Zega (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: Civility is an attitude of mutual respect and tolerance for differences that influences the professionalism of a nurse. However, there is a rise in incivility in nursing, including aggressive behavior, a lack of discipline, and failure to follow rules. Nursing education and practice are critical for promoting civil behavior through effective communication, conflict management, and resolution.Purpose: To determine strategies for promoting civility in nursing education and practice.Method: This study utilized a simplified approach to conduct a systematic review of the literature. The databases used were PubMed, Google Scholar, Science Direct (Elsevier), and EBSCO. Civility, incivility, promoting civility, and nursing were used as keywords.Results: This study identified two major themes: